Reduced Glomerular Filtration in Diabetes Is Attributable to Loss of Density and Increased Resistance of Glomerular Endothelial Cell Fenestrations. Issue 6 (June 2022) - Finch, Natalie C.; Fawaz, Sarah S.; Neal, Chris R.; Butler, Matthew J.; Lee, Vivian K.; Salmon, Andrew J.; Lay, Abigail C.; Stevens, Megan; Dayalan, Lusyan; Band, Hamid; Mellor, Harry H.; Harper, Steven J.; et al.
Significance Statement: We propose a novel mechanism underlying loss of renal filtration function from studying glomerular endothelial cell (GEnC) fenestrae in human diabetic kidney tissue and in a mouse model of diabetes. Diaphragmed fenestrae may provide structural resistance to filtration. We hypothesize that EHD3 is a key regulator of GEnC fenestrations, and its glomerular expression is lost in diabetes. This study establishes the critical role of GEnC fenestrations in renal filtration function and suggests a key regulator, potentially paving the way for development of targeted therapies to restore fenestrae and thus filtration function in kidney disease. Visual Abstract: Abstract : Background: Glomerular endothelial cell (GEnC) fenestrations are recognized as an essential component of the glomerular filtration barrier, yet little is known about how they are regulated and their role in disease. Methods: We comprehensively characterized GEnC fenestral and functional renal filtration changes including measurement of glomerular K f and GFR in diabetic mice (BTBR ob − /ob − ). We also examined and compared human samples. We evaluated Eps homology domain protein-3 (EHD3) and its association with GEnC fenestrations in diabetes in disease samples and further explored its role as a potential regulator of fenestrations in an in vitro model of fenestration formation using b.End5 cells. Results: Loss of GEnC fenestration density was associated with decreased filtration function in diabetic nephropathy. We identified increased diaphragmed fenestrations in diabetes, which are posited to increase resistance to filtration and further contribute to decreased GFR. We identified decreased glomerular EHD3 expression in diabetes, which was significantly correlated with decreased fenestration density. Reduced fenestrations in EHD3 knockdown b.End5 cells in vitro further suggested a mechanistic role for EHD3 in fenestration formation. Conclusions: This study demonstrates the critical role of GEnC fenestrations in renal filtration function and suggests EHD3 may be a key regulator, loss of which may contribute to declining glomerular filtration function through aberrant GEnC fenestration regulation. This points to EHD3 as a novel therapeutic target to restore filtration function in disease.